2010
DOI: 10.1007/s11764-010-0120-3
|View full text |Cite
|
Sign up to set email alerts
|

Toward a cancer-specific model of psychological distress: population data from the 2003–2005 National Health Interview Surveys

Abstract: Identifying and understanding correlates of clinically meaningful distress may improve efforts to prevent, identify, and treat significant distress in cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 72 publications
3
80
2
Order By: Relevance
“…Spouses of these married patients may encourage them to perform surgery versus expectant management 28, which could partly account for the discrepancies. Studies showed diagnosis of cancer caused more distress than other diseases 29. Married people were easier to benefit from social support from their friends and family and displayed less distress and depression after the cancer diagnosis 30.…”
Section: Discussionmentioning
confidence: 99%
“…Spouses of these married patients may encourage them to perform surgery versus expectant management 28, which could partly account for the discrepancies. Studies showed diagnosis of cancer caused more distress than other diseases 29. Married people were easier to benefit from social support from their friends and family and displayed less distress and depression after the cancer diagnosis 30.…”
Section: Discussionmentioning
confidence: 99%
“…25 Serious, debilitating psychological distress is rare, with an estimated prevalence of 2–3% among well adults 26 , and with higher prevalence among adults with chronic or life-threatening illness. 27 Parental PD is reported as mean K6 scores and as proportion of parents with SPD.…”
Section: Methodsmentioning
confidence: 99%
“…The covariates included sociodemographic variables - age at cancer diagnosis in years, gender, 2 education level, ethnicity, and marital status (Kaiser, Hartoonian, & Owen, 2010); cancer-related variables – cancer type, stage of disease at diagnosis, type of treatment received, health status, and progression to more severe disease (Arora, Finney Rutten, Gustafson, Moser, & Hawkins, 2007; Kolva, Rosenfeld, Pessin, Breitbart, & Brescia, 2011); and psychological variables – prior self-reported experience of anxiety or depression and the Lerman Cancer Worry Scale (Lerman et al, 1991). …”
Section: Methodsmentioning
confidence: 99%